Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor and its application

By using Ag3PO4-UiO-66/apt/GO/GCE in an electrochemiluminescence sensor, the complexity and high cost of detecting diethylstilbestrol in the prior art is solved by using the resonance energy transfer mechanism between Ag3PO4-UiO-66 and GO. The problem of this achieves high sensitivity, rapid and economical detection results.

CN115479979BActive Publication Date: 2025-02-25CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211082691.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-06
Publication Date
2025-02-25
Estimated Expiration
2042-09-06

AI Technical Summary

Technical Problem

The prior art methods for detecting diphenestrol require special instruments, are complex in operation and costly, and are insufficient in sensitivity and response speed.

Method used

Ag3PO4-UiO-66/apt/GO/GCE electrochemiluminescence sensor is used to achieve quantitative detection of diethylstilbestrol through the resonant energy transfer mechanism between Ag3PO4-UiO-66 and GO.

Benefits of technology

Improve detection sensitivity and speed, reduce costs, simplify operations, and expand the linear detection range to achieve high sensitivity detection of diethylstilbestrol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115479979B_ABST
    Figure CN115479979B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electrochemical detection technology, and relates to an Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor and its application. The sensor comprises a glassy carbon electrode, the outer surface of which is modified in sequence by Ag3PO4-UiO-66 as a resonance energy donor, apt, a ligand adapted to an object to be detected, and GO as a resonance energy receptor, and Ag3PO4-UiO-66 and GO are connected by apt; Ag3PO4-UiO-66 is a UiO-66 material loaded by Ag3PO4. The sensor has the advantages of high detection sensitivity, fast detection speed, strong specificity, wide linear range, and easy use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical detection, and relates to a Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor and applications thereof. Background Art

[0002] Electrochemiluminescence (ECL), also known as electrochemiluminescence, has attracted widespread attention in recent years due to its advantages such as high sensitivity, good reproducibility, good selectivity and wide linear range. It can be applied to clinical diagnosis, food analysis and other aspects. Diethylstilbestrol (DES) is an environmental endocrine disruptor. Traditional detection methods for DES usually include: high performance liquid chromatography (HPLC), gas chromatography-tandem mass spectrometry, fluorescence, electrochemical fluorescence and high performance liquid chromatography-mass spectrometry (HPLC-MS). However, most of these methods require special instruments, long working time, cumbersome pretreatment, and high related costs. Compared with these methods, electrochemical analysis has the advantages of high sensitivity, fast response speed, low cost and simple operation. It has been widely used in the detection of drugs, pesticides, molds, etc., and has attracted people's attention. Electrochemiluminescence has the characteristics of high sensitivity, high resolution, multi-substance detection, low instrument price and small amount of detection material, and has been widely used in the field of analysis.

[0003] Resonance energy transfer is an emerging molecular spectroscopy method, specifically referring to the transfer of electronic excitation energy between energy donors and energy acceptor pairs. Electrochemiluminescence-resonance energy transfer (ECL-RET) combines the advantages of both and is a new field with great development potential. It has low background noise and avoids the influence of scattered light, and has been widely used in the construction of biosensors. Therefore, this study selected diethylstilbestrol as the detection object, modified the luminophore on the surface of the glassy carbon electrode (GCE), and achieved sensitive detection of diethylstilbestrol through resonance energy transfer formed by aptamer-linked receptors.

[0004] In order to enhance the sensitivity of the sensor, the luminophore can be modified. In recent years, metal organic frameworks (MOFs) have attracted more and more attention as modified electrode materials due to their large specific surface area, suitable pore volume, ordered structure and high biocompatibility. Summary of the invention

[0005] One of the purposes of the present invention is to provide a highly sensitive Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor in order to further improve the detection sensitivity of a substance. Based on the resonance energy transfer mechanism between Ag3PO4-UiO-66 and GO, quantitative detection of the target is achieved. The sensor has the advantages of high detection sensitivity, fast detection speed, and easy use.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions:

[0007] The Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor is used as a working electrode in electrochemiluminescence detection, including a glassy carbon electrode, the outer surface of which is modified in sequence by Ag3PO4-UiO-66 as a resonance energy donor, a ligand apt adapted to the analyte, and GO as a resonance energy acceptor, and Ag3PO4-UiO-66 and GO are connected by apt; Ag3PO4-UiO-66 is a UiO-66 material loaded with Ag3PO4.

[0008] The Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescent sensor provided by the present invention has a resonance energy transfer mechanism between Ag3PO4-UiO-66 and GO. Since there is a large overlap area between the electrochemiluminescent emission spectrum of Ag3PO4-UiO-66 (donor) and the ultraviolet visible absorption spectrum of GO (acceptor), there is a resonance energy transfer mechanism between the two, and the concentration of added diethylstilbestrol has a linear relationship with the increased light intensity. This greatly improves the sensitivity of electrochemiluminescent analysis, enhances specificity, and broadens the linear range.

[0009] Compared with Au NCs, Au NPs, and Au NBs, GO not only 4- The ECL intensity of UiO-66 is quenched, and GO can act as an acceptor to Ag3PO 4- The ECL intensity of UiO-66 quenches and then recovers, and in the presence of the analyte, it peels off to produce the ECL-RET effect, realizing the detection of the analyte. When the resonance energy donor is Ag3PO4-Cu-MOF, GO can quench its ECL intensity, but it cannot recover.

[0010] Furthermore, the mass ratio of Ag3PO4-UiO-66 to GO is 2:1.

[0011] Furthermore, the preparation method of Ag3PO4-UiO-66 / apt / GO / GCE includes: polishing a glassy carbon electrode, ultrasonicating with nitric acid, anhydrous ethanol and deionized water respectively, and drying naturally for use; using a microinjector to pipette an ethanol solution of Ag3PO4-UiO-66 and drop it on the surface of the glassy carbon electrode, and drying at room temperature to obtain an Ag3PO4-UiO-66 / GCE modified electrode; dropping apt and GO on the surface of the Ag3PO4-UiO-66 / GCE electrode activated by EDC·NHS to obtain the Ag3PO4-UiO-66 / apt / GO / GCE.

[0012] Furthermore, the preparation method of Ag3PO4-UiO-66 comprises the following steps:

[0013] S1. UiO-66 was fully dispersed in deionized water by ultrasound, and then AgNO3 was added to dissolve and mix thoroughly to obtain a mixture A.

[0014] S2. Add Na2HPO4 solution dropwise into mixture A, stir to mix and perform ultrasound; centrifuge, wash and dry to obtain the Ag3PO4-UiO-66.

[0015] The larger specific surface area of ​​UiO-66 provides an excellent platform for the loading of Ag3PO4. Ag3PO4 has excellent luminescence properties, and UiO-66 has a larger specific surface area, so the light intensity of Ag3PO4 can be significantly improved after compounding.

[0016] Furthermore, UiO-66 can be prepared by the following method: ZrCl4 and terephthalic acid are dissolved in DMF to prepare a mixed solution, which is then transferred to a polytetrafluoroethylene autoclave. The reaction is continued at 120°C for 48 hours. After the reaction is completed, the mixture is cooled to room temperature. The liquid in the autoclave is removed, washed with DMF and methanol in turn, and centrifuged and dried to obtain UiO-66.

[0017] Furthermore, the preparation method of GO comprises the following steps:

[0018] A1. Mix concentrated sulfuric acid, natural flake graphite, potassium nitrate and potassium permanganate in a three-necked flask and stir for 3 to 5 hours to obtain a blue-green viscous mixture;

[0019] A2. Place the mixture in a 30°C constant temperature water bath for about 1 to 2 hours, and the reaction solution becomes a slurry;

[0020] A3. After stirring in an ice-water bath for 5 minutes, add a small amount of hydrochloric acid solution and hydrogen peroxide solution to obtain a brown-yellow mixed solution;

[0021] A4. Aspirate the supernatant and wash with water until it becomes neutral. Then dialyze with a dialysis bag to obtain a relatively pure GO solution.

[0022] Furthermore, the drop coating amount of the ethanol solution of Ag3PO4-UiO-66 was 5.0 μL, and the concentration was 1.0 mg / mL; the drop coating amount of GO was 2.5 μL, and the concentration was 1.0 mg / mL.

[0023] Furthermore, the amount of apt added was 2.5 μL and the concentration was 1 μM. Apt has amino groups and combines with Ag3PO4-UiO-66 through amide bonds, and GO is adsorbed on the surface of apt through electrostatic adsorption.

[0024] The second object of the present invention is to provide an application of the above-mentioned Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor, which is specifically used for the detection of environmental endocrine disruptors in water bodies, such as nonylphenol, herbicide ether, bisphenol A, bisphenol F, diethylstilbestrol, etc.

[0025] The present invention also provides a method for detecting diethylstilbestrol based on the Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor, comprising the following steps:

[0026] Ag3PO4-UiO-66 / apt / GO / GCE was used as the working electrode for electrochemiluminescence test, platinum electrode was used as the auxiliary electrode, and Ag / AgCl was used as the reference electrode to form a three-electrode system for electrochemiluminescence detection of diethylstilbestrol, and apt was 5'-NH2-GGC GAT GGG GTA GGG GGT GTG GAG GGG CCG GAC GGA GGG G-3'.

[0027] As a preferred embodiment of the above technical solution, the specific steps are as follows:

[0028] B1. Preparation of phosphate buffer solution containing potassium persulfate;

[0029] B2. The concentration range is 1.0×10 -14 mol / L~1.0×10 -3 mol / L series of different concentrations of diethylstilbestrol standard solutions:

[0030] Specifically, diethylstilbestrol was prepared with deionized water at 1.0×10 -3 mol / L solution was diluted into a series of diethylstilbestrol standard solutions with different concentrations ranging from 1.0×10 -14 mol / L~1.0×10 -3 mol / L;

[0031] B3. Drawing of standard curve:

[0032] The modified electrode Ag3PO4-UiO-66 / apt / GO / GCE was used as the working electrode, the platinum electrode was used as the auxiliary electrode, and Ag / AgCl was used as the reference electrode to form a three-electrode system. The three-electrode system was placed in a series of diethylstilbestrol standard solutions of different concentrations prepared in step B2 and immersed for a certain period of time, and then the three-electrode system was placed in a phosphate buffer solution containing potassium persulfate to detect the luminescence intensity. Within the electrochemical window range of -1.8 to 0V, the photomultiplier tube was used at a high voltage of 800V and a scan rate of 0.1V / s to perform cyclic voltammetry scanning, and the time-luminescence intensity curve was recorded. The linear relationship between the difference in luminescence intensity before and after the addition of diethylstilbestrol and the logarithmic value of the diethylstilbestrol concentration was established to obtain the corresponding linear regression equation;

[0033] B4. Detection range and detection limit:

[0034] According to the test results of step B3, the concentration of diethylstilbestrol was 1.0×10 -14 mol / L~1.0×10 -8 mol / L has a good linear relationship. The minimum detection limit is 7.2×10 -15 mol / L.

[0035] As a preferred embodiment of the above technical solution, the Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor modified electrode was placed in a refrigerator at 4°C for 12 hours for incubation, and then a three-electrode system was prepared.

[0036] In summary, the present invention has the following beneficial effects:

[0037] The present invention discloses a preparation method and application method of a working electrode for detecting diethylstilbestrol by electrochemiluminescence method, which realizes the quantitative detection of diethylstilbestrol based on the resonance energy transfer mechanism between Ag3PO4-UiO-66 and GO. The minimum detection range of Ag3PO4-UiO-66 / apt / GO / GCE provided by the present invention is 1×10 -14 mol / L, the detection limit is 7.2×10 -15 mol / L.

[0038] The sensor has the advantages of high detection sensitivity, fast detection speed, strong specificity, wide linear range and easy use. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0040] Figure 1 It is a brief flow chart and mechanism diagram of the preparation of the sensor in the invention and the detection of diethylstilbestrol;

[0041] Figure 2 It is the linear curve of the luminescence intensity after adding different concentrations of diethylstilbestrol, a~h: 0mol / L, 1.0×10 - 14 mol / L, 1.0×10 -13 mol / L, 1.0×10 -12 mol / L, 1.0×10 -11 mol / L, 1.0×10 -10 mol / L, 1.0×10 - 9mol / L, 1.0×10 -8 mol / L;

[0042] Figure 3 It is the standard curve of the difference in luminescence intensity before and after adding diethylstilbestrol and the logarithm of diethylstilbestrol concentration.

[0043] Figure 4 This is the ECL performance curve of electrodes modified with different materials.

[0044] Figure 5 It is the ECL spectrum of the luminescent material Ag3PO4-UiO-66 and the UV spectrum of the acceptor GO. DETAILED DESCRIPTION

[0045] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the present invention is further described by taking the detection of diethylstilbestrol as an example, and its specific implementation methods, features and effects are described in detail as follows. The present invention is not limited to the following specific implementation methods. A person of ordinary skill in the art can adopt other various specific implementation methods to implement the present invention according to the content disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.

[0046] Embodiment: A preparation method and application method of an electrochemiluminescence sensor for detecting diethylstilbestrol with high sensitivity.

[0047] A method for preparing an electrochemiluminescent sensor for detecting diethylstilbestrol with high sensitivity:

[0048] (1) Preparation method of Ag3PO4-UiO-66:

[0049] S1.1.0×10 -3 mol ZrCl4 and 1.0×10 -3 1 mol of terephthalic acid was dissolved in DMF to prepare 38.7 mL of a mixed solution. The dissolved mixture was transferred to a polytetrafluoroethylene autoclave. The reaction was continued at 120°C for 48 h. After the reaction was completed, the mixture was cooled to room temperature. The liquid in the autoclave was removed, washed with DMF and methanol in turn, centrifuged at 8000 rpm for 15 min, and vacuum dried at 120°C for 24 h to obtain UiO-66.

[0050] S2. 10 mg of UiO-66 was dissolved in deionized water, and after ultrasonic treatment for 1 h, 2.5 mL of 0.6 M AgNO3 was added to obtain mixture A;

[0051] S3. The mixture A obtained in step S1 was stirred at room temperature to mix thoroughly;

[0052] S4. 2.5 mL of 0.2 M Na2HPO4·12H2O was added dropwise to the mixture A solution, stirred and mixed at 30°C and ultrasonicated; after centrifugation at 10,000 rpm for 15 min, the Ag3PO4-UiO-66 was obtained by drying at 60°C.

[0053] (2) Preparation method of GO:

[0054] A1. Mix 50 mL of concentrated sulfuric acid, 1 g of natural flake graphite, 0.5 g of potassium nitrate and 6 g of potassium permanganate in a three-necked flask and stir for 3 to 5 hours to obtain a blue-green viscous mixture;

[0055] A2. Place the above mixture in a constant temperature water bath at 30°C for about 1 to 2 hours, and the reaction will become a slurry;

[0056] A3. After stirring in an ice-water bath for 5 min, add 500 mL of 5% hydrochloric acid solution and 300 mL of 5% hydrogen peroxide solution to obtain a brown-yellow mixed solution;

[0057] A4. Aspirate the supernatant and wash with water until it becomes neutral. Then dialyze with a dialysis bag to obtain a relatively pure GO solution.

[0058] (3) Preparation method of modified electrode Ag3PO4-UiO-66 / apt / GO / GCE:

[0059] The glassy carbon electrode was polished, ultrasonicated with nitric acid, anhydrous ethanol and deionized water respectively, and dried naturally for use. The ethanol solution of Ag3PO4-UiO-66 was transferred to the surface of the glassy carbon electrode with a microinjector and dried at room temperature to obtain the Ag3PO4-UiO-66 / GCE modified electrode; the apt solution was added to the surface of the Ag3PO4-UiO-66 / GCE activated with EDC·NHS, and incubated in a refrigerator at 4°C for 12 hours to obtain the Ag3PO4-UiO-66 / apt / GCE; finally, GO was modified on the surface of the Ag3PO4-UiO-66 / apt / GCE to obtain the Ag3PO4-UiO-66 / apt / GO / GCE modified electrode, that is, the ECL sensor was obtained.

[0060] An application method of a working electrode for detecting diethylstilbestrol by electrochemiluminescence method:

[0061] B1. Preparation of phosphate buffer solution containing potassium persulfate;

[0062] B2. Preparation of standard solutions containing different concentrations of diethylstilbestrol:

[0063] Diethylstilbestrol was prepared with anhydrous ethanol at a concentration of 1.0 × 10 -3mol / L solution was diluted into a series of diethylstilbestrol standard solutions with different concentrations ranging from 1.0×10 -14 mol / L~1.0×10 -3 mol / L;

[0064] B3. Drawing of standard curve

[0065] The modified electrode Ag3PO4-UiO-66 / apt / GO / GCE was used as the working electrode, the platinum electrode as the auxiliary electrode, and Ag / AgCl as the reference electrode to form a three-electrode system. The three-electrode system was placed in 0.1 mol / L PBS buffer at pH = 7.4 containing 0.05 mol / L K2S2O8 as a blank solution to detect the luminescence intensity.

[0066] The three-electrode system was placed in a series of diethylstilbestrol standard solutions (1.0×10 -14 mol / L, 1.0×10 -13 mol / L, 1.0×10 -12 mol / L, 1.0×10 -11 mol / L, 1.0×10 -10 mol / L, 1.0×10 -9 mol / L, 1.0×10 -8 Then, the three-electrode system was placed in a 0.1 mol / L PBS buffer solution with a pH of 7.4 and containing 0.05 mol / L K2S2O8. In the electrochemical window range of -1.8 to 0 V, the photomultiplier tube was set at a high voltage of 800 V and a scan rate of 0.1 V / s to perform cyclic voltammetry scanning. The time-luminescence intensity curve (T-ECL) was recorded. The linear relationship between the difference in luminescence intensity before and after the addition of diethylstilbestrol and the logarithmic value of the diethylstilbestrol concentration was established, and the corresponding linear regression equation was obtained as follows: △I ECL =2722.90+479.18Log C (nmol / L), the correlation coefficient (R) is 0.9948. The detection range of the linear regression equation is 1.0×10 -14 ~1.0×10 -8 mol / L, the minimum detection limit is 7.2×10 -15 mol / L.

[0067] Based on the above examples, experiments of Comparative Examples 1 to 6 were also conducted, as shown in Table 1:

[0068] Table 1 Determination results of diethylstilbestrol with different modifications

[0069]

[0070]

[0071] From Table 1 we can see that:

[0072] (1) Controlling the stirring time of the preparation has almost no effect on Ag3PO4-UiO-66. The intensity of Ag3PO4-Cu-MOF tested under the same conditions is lower than that of the luminophore used in this application, and shortening the preparation time has a great influence on the performance.

[0073] (2) Comparative Examples 1 to 6 were tested using different receptors. Au NCs, Au NPs, Au NBs and GO can all react with Ag3PO 4- The ECL intensity of UiO-66 is quenched, but GO can be stripped in the presence of diethylstilbestrol to produce ECL-RET effect, realizing the detection of DES. Au NCs, Au NPs, and Au NBs can only quench but not rebound.

[0074] (3) Comparative study on the quenching effect of GO on Ag3PO4-Cu-MOF shows that GO can quench the ECL intensity of Ag3PO4-Cu-MOF, but it cannot recover. It is not a simple replacement of the same type for detection.

[0075] Comparative Example 7:

[0076] (1) Preparation method of Ag3PO4-UiO-66 / GCE:

[0077] The glassy carbon electrode was polished, ultrasonicated with nitric acid, anhydrous ethanol, and deionized water, and dried naturally for use. 5 μL of 1.0 mg / mL ethanol solution of Ag3PO4-UiO-66 material was pipetted with a microinjector and dropped onto the surface of the clean glassy carbon electrode, and dried at room temperature to obtain the Ag3PO4-UiO-66 / GCE modified electrode, which was used as the working electrode for electrochemiluminescence test.

[0078] (2) Drawing of standard curve

[0079] The three-electrode system was composed of Ag3PO4-UiO-66 / GCE modified electrode as the working electrode, platinum electrode as the auxiliary electrode, and Ag / AgCl as the reference electrode. The luminescence intensity was detected using 0.1 mol / L PBS buffer solution with pH = 7.4 containing 0.05 mol / L K2S2O8 as the blank solution. The three-electrode system was placed in a series of diethylstilbestrol concentrations (1.0×10 -14 mol / L, 1.0×10 -13 mol / L, 1.0×10 -12 mol / L, 1.0×10 -11 mol / L, 1.0×10 -10mol / L, 1.0×10 -9 mol / L, 1.0×10 -8 After soaking in a standard solution of 10 mol / L for a period of time, cyclic voltammetry scanning was performed in the electrochemical window range of -1.8 to 0 V, with a photomultiplier tube high voltage of 800 V and a scan rate of 0.1 V / s in a 0.1 mol / L PBS buffer solution with a pH of 7.4 containing 0.05 mol / L K2S2O8, and T-ECL curves were recorded. A linear relationship between the difference in luminescence intensity before and after the addition of diethylstilbestrol and the logarithmic value of the diethylstilbestrol concentration was established, and the corresponding linear regression equation was obtained.

[0080] Comparative Example 8:

[0081] (1) Preparation method of GO / apt / GCE:

[0082] The glassy carbon electrode was polished, ultrasonicated with nitric acid, anhydrous ethanol and deionized water respectively, and dried naturally for use. 5 μL of 1.0 mg / mL GO material ethanol solution was pipetted with a microinjector and dropped onto the surface of the clean glassy carbon electrode, dried at room temperature to obtain a GO / GCE modified electrode, and 2.5 μL of 1.0 μM apt was modified on the GO / GCE surface and incubated for 12 h to obtain GO / apt / GCE as the working electrode for electrochemiluminescence test.

[0083] (2) Drawing of standard curve

[0084] The GO / apt / GCE modified electrode was used as the working electrode, the platinum electrode as the auxiliary electrode, and the Ag / AgCl as the reference electrode to form a three-electrode system. The luminescence intensity was detected using a 0.1 mol / L PBS buffer solution with a pH of 7.4 and containing 0.05 mol / L K2S2O8 as the blank solution. The three-electrode system was placed in a series of diethylstilbestrol concentrations (1.0×10 -14 mol / L, 1.0×10 - 13 mol / L, 1.0×10 -12 mol / L, 1.0×10 -11 mol / L, 1.0×10 -10 mol / L, 1.0×10 -9 mol / L, 1.0×10 - 8After a period of time in a standard solution of 1.5 mol / L, a cyclic voltammetric scan was performed in a 0.1 mol / L PBS buffer solution with pH=7.4 and a photomultiplier tube high voltage of 800 V and a scan rate of 0.1 V / s in an electrochemical window range of -1.8 to 0 V, and a T-ECL curve was recorded. A linear relationship between the difference in luminescence intensity before and after the addition of diethylstilbestrol and the logarithmic value of the diethylstilbestrol concentration was established, and the corresponding linear regression equation was obtained.

[0085] Comparative Example 9:

[0086] (1) Preparation method of Ag3PO4-UiO-66 / apt / GCE:

[0087] The glassy carbon electrode was polished, ultrasonicated with nitric acid, anhydrous ethanol and deionized water respectively, and dried naturally for use. 5 μL of 1.0 mg / mL ethanol solution of Ag3PO4-UiO-66 material was pipetted with a microinjector and dropped onto the surface of a clean glassy carbon electrode and dried at room temperature to obtain an Ag3PO4-UiO-66 / GCE modified electrode. 2.5 μL of 1.0 μM apt was modified on the surface of Ag3PO4-UiO-66 / GCE, and 2.5 μL of 1.0 μM apt was modified on the surface of Ag3PO4-UiO-66 / GCE, incubated for 12 hours, and Ag3PO4-UiO-66 / apt / GCE was obtained as the working electrode for electrochemiluminescence test.

[0088] (2) Drawing of standard curve

[0089] The three-electrode system was composed of Ag3PO4-UiO-66 / apt / GCE modified electrode as the working electrode, platinum electrode as the auxiliary electrode, and Ag / AgCl as the reference electrode. The luminescence intensity was detected using 0.1 mol / L PBS buffer solution with pH = 7.4 containing 0.05 mol / L K2S2O8 as the blank solution. The three-electrode system was placed in a series of diethylstilbestrol concentrations (1.0×10 -14 mol / L, 1.0×10 -13 mol / L, 1.0×10 -12 mol / L, 1.0×10 -11 mol / L, 1.0×10 -10 mol / L, 1.0×10 -9 mol / L, 1.0×10 -8After a period of time in a standard solution of 1.5 mol / L, a cyclic voltammetric scan was performed in a 0.1 mol / L PBS buffer solution with pH=7.4 and a photomultiplier tube high voltage of 800 V and a scan rate of 0.1 V / s in an electrochemical window range of -1.8 to 0 V, and a T-ECL curve was recorded. A linear relationship between the difference in luminescence intensity before and after the addition of diethylstilbestrol and the logarithmic value of the diethylstilbestrol concentration was established, and the corresponding linear regression equation was obtained.

[0090] Table 2 Determination results of known content of diethylstilbestrol

[0091]

[0092]

[0093] As shown in Table 2, the sample was tested three times in parallel, the relative standard deviation was less than 5%, and the spike recovery range was 97% to 101%. The above results show that the glassy carbon electrode modified with Ag3PO4-UiO-66 or GO alone without modification with Ag3PO4-UiO-66 / apt / GO composite material cannot detect diethylstilbestrol, while the working electrode and application method provided by the present invention can detect diethylstilbestrol sensitively, quickly and accurately.

[0094] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor, used as working electrode in electrochemiluminescence detection, characterized by: The invention comprises a glassy carbon electrode, the outer surface of which is modified by Ag3PO4-UiO-66 as a resonance energy donor, apt, a ligand adapted to the object to be tested, and GO as a resonance energy acceptor in sequence, and Ag3PO4-UiO-66 and GO are connected by apt; Ag3PO4-UiO-66 is a UiO-66 material loaded with Ag3PO4; The preparation method of Ag3PO4-UiO-66 / apt / GO / GCE comprises the following steps: polishing a glassy carbon electrode, ultrasonicating with nitric acid, anhydrous ethanol and deionized water respectively, and drying naturally for use; using a microinjector to pipette an ethanol solution of Ag3PO4-UiO-66 and dripping it on the surface of the glassy carbon electrode, and drying it at room temperature to obtain an Ag3PO4-UiO-66 / GCE modified electrode; dripping apt and GO on the surface of the Ag3PO4-UiO-66 / GCE electrode activated by EDC·NHS to obtain the Ag3PO4-UiO-66 / apt / GO / GCE; The preparation method of Ag3PO4-UiO-66 comprises the following steps: S1. UiO-66 was fully dispersed in deionized water by ultrasound, and then AgNO3 was added to fully dissolve and mix to obtain a mixture A; S2. Na2HPO4 solution was added dropwise to the mixture A, stirred and mixed, and ultrasonicated; centrifuged, washed, and dried to obtain the Ag3PO4-UiO-66.

2. The Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor according to claim 1, characterized in that: The mass ratio of Ag3PO4-UiO-66 to GO is 2:

1.

3. The Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor according to claim 1, characterized in that: The drop coating amount of the Ag3PO4-UiO-66 was 5.0 μL, and the concentration was 1.0 mg / mL; the drop coating amount of the GO was 2.5 μL, and the concentration was 1.0 mg / mL.

4. The use of the Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor according to any one of claims 1 to 3, characterized in that: Used for the detection of environmental endocrine disruptors in water bodies.

5. The use of the Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor according to claim 4, characterized in that: The environmental endocrine disruptor is diethylstilbestrol, and the detection method includes: Ag3PO4-UiO-66 / apt / GO / GCE as the working electrode of the electrochemiluminescence test, a platinum electrode as the auxiliary electrode, and Ag / AgCl as the reference electrode to form a three-electrode system for electrochemiluminescence detection of diethylstilbestrol, and apt is 5'-NH2-GGC GAT GGG GTA GGG GGT GTG GAG GGGCCG GAC GGA GGG G-3'.

6. The use of the Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor according to claim 5, characterized in that: The following steps are also included: B1. Preparation of phosphate buffer solution containing potassium persulfate; B2. The concentration range is 1.0×10 -14 mol / L ~ 1.0×10 -3 mol / L series of diethylstilbestrol standard solutions with different concentrations; B3. Drawing of standard curve: The modified electrode Ag3PO4-UiO-66 / apt / GO / GCE was used as the working electrode, the platinum electrode was used as the auxiliary electrode, and the Ag / AgCl was used as the reference electrode to form a three-electrode system. The three-electrode system was immersed in a series of diethylstilbestrol standard solutions with different concentrations prepared in step B2 for a certain period of time, and the luminescence intensity was detected using a phosphate buffer solution containing potassium persulfate as a blank solution. In the electrochemical window range of -1.8 ~ 0 V, a photomultiplier tube high voltage of 800 V and a scan rate of 0.1 V / s were used to perform cyclic voltammetry scanning, and the time-luminescence intensity curve was recorded. The linear relationship between the difference in luminescence intensity before and after the addition of diethylstilbestrol and the logarithm of the diethylstilbestrol concentration was established, and the corresponding linear regression equation was obtained.

7. The use of the Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor according to claim 5, characterized in that: The Ag3PO4-UiO-66 / apt / GO / GCE electrochemiluminescence sensor was placed in a refrigerator at 4°C for 12 h before preparing the three-electrode system.

Citation Information

Patent Citations

  • Sensor for detecting acetamiprid based on electrochemical luminescence method as well as preparation method and application

    CN112098484A

  • Sensor used for detecting diethylstilbestrol by using electrochemiluminescence method and based on resonance energy transfer, and preparation method and application of sensor

    CN112114018A